2021
DOI: 10.1038/s43587-021-00027-5
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of SIRT3 gene expression by airway delivery resolves age-associated persistent lung fibrosis in mice

Abstract: Aging is a risk factor for progressive fibrotic disorders involving diverse organ systems, including the lung. Idiopathic pulmonary fibrosis, an age-associated degenerative lung disorder, is characterized by persistence of apoptosis-resistant myofibroblasts. Here we demonstrate that sirtuin 3 (SIRT3), a mitochondrial deacetylase, is downregulated in the lungs of humans with idiopathic pulmonary fibrosis and in mice subjected to lung injury. Overexpression of Sirt3 cDNA via airway delivery restored the capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
(93 reference statements)
2
37
0
Order By: Relevance
“…SIRT3 may attenuate pro-fibrotic signaling in other cells within these fibrosis-promoting distal lung niches. Consistent with this notion is that SIRT3 deficiency is evident in the AECs and fibroblasts of patients with IPF as well as aged mice [32,33,35]. Notably, a recent study showed that airway delivery of a Sirt3 overexpression cDNA promotes resolution of lung fibrosis in aged mice in part by working along with macrophage-derived paracrine secreted products in activating the forkhead box (FOX) transcription factor FoxO3a in fibroblasts, which subsequently augments fibroblast pro-apoptotic Bcl2 family member expression and apoptosis [35].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…SIRT3 may attenuate pro-fibrotic signaling in other cells within these fibrosis-promoting distal lung niches. Consistent with this notion is that SIRT3 deficiency is evident in the AECs and fibroblasts of patients with IPF as well as aged mice [32,33,35]. Notably, a recent study showed that airway delivery of a Sirt3 overexpression cDNA promotes resolution of lung fibrosis in aged mice in part by working along with macrophage-derived paracrine secreted products in activating the forkhead box (FOX) transcription factor FoxO3a in fibroblasts, which subsequently augments fibroblast pro-apoptotic Bcl2 family member expression and apoptosis [35].…”
Section: Discussionmentioning
confidence: 79%
“…Although the causal role of lung recruitment of Mo-AMs in mediating lung fibrosis is established, the precise molecular mechanisms involved are unclear and an area of ongoing study by our group and others [35,[40][41][42][55][56][57][58]. Using the asbestos lung fibrosis model with a combination of confocal microscopy and single-cell RNA sequencing, our group reported that Mo-AMs are recruited to fibrotic areas of the lungs, engulf asbestos fibers, and provide a connection between injured alveolar epithelium and activated fibroblasts by localizing in spatially restricted pro-fibrotic niches [41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations